2010
DOI: 10.1681/asn.2009080876
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Urinary Peptidomics in Renal Transplantation Identifies Biomarkers for Acute Rejection

Abstract: Noninvasive methods to diagnose rejection of renal allografts are unavailable. Mass spectrometry followed by multiple-reaction monitoring provides a unique approach to identify disease-specific urine peptide biomarkers. Here, we performed urine peptidomic analysis of 70 unique samples from 50 renal transplant patients and 20 controls (n ϭ 20), identifying a specific panel of 40 peptides for acute rejection (AR). Peptide sequencing revealed suggestive mechanisms of graft injury with roles for proteolytic degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 46 publications
1
91
0
3
Order By: Relevance
“…In that regard, a recent study using a urinary peptidomics approach has identified MMP-7 as one of the biomarkers for acute rejection in renal transplantation. 42 Similarly, plasma MMP-7 is proposed as a potential biomarker in human idiopathic pulmonary fibrosis and as a metastatic marker and survival predictor in patients with renal cell carcinomas. 13,43 Whether plasma MMP-7 level is also elevated in the fibrotic kidney diseases remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In that regard, a recent study using a urinary peptidomics approach has identified MMP-7 as one of the biomarkers for acute rejection in renal transplantation. 42 Similarly, plasma MMP-7 is proposed as a potential biomarker in human idiopathic pulmonary fibrosis and as a metastatic marker and survival predictor in patients with renal cell carcinomas. 13,43 Whether plasma MMP-7 level is also elevated in the fibrotic kidney diseases remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, all but one of the studies presented results based on the whole cohort of patients recruited, in the absence of internal or external validation. Using a urinary peptide biomarker panel, Ling et al recently reported a sensitivity of 80% and specificity of 83% in detecting acute rejection in a test set of 24 participants; the main caveat was that the nonrejectors were patients with stable renal function or patients with BK nephropathy, a control group relevant for research but not for clinical application of the test (21).…”
Section: Discussionmentioning
confidence: 99%
“…THP is the most abundant protein in urine, but its function remains unclear 68 ; it has been implicated as a biomarker of kidney disease and allograft rejection 69,70 and may be a damage signal in renal tubular injury. THP promotes cytokine release 71 and immune cell activation, including DC maturation, 72 but may also have a protective anti-inflammatory role.…”
Section: Heat-shock Proteinsmentioning
confidence: 99%